Factors Related to Socio-Economic and Parenting Patterns with Malnutrition in Toddler at Kori Health Center - Lodong, Fabiola Densi; Talahatu, Anna Heny; Jutomo, Lewi (Timorese Journal of Public Health, 2022)
Malnutrition is a state of severe lack of energy and protein due to insufficient consumption of nutritious food and or poor parenting that affects the nutritional status of childrenn under five. The purpose of this study was to determine the relationship between socio-economic variables and parenting patterns with the incidence of malnutrition in children under five in the operational area of the Kori Health Center, Southwest Sumba Regency. The research method uses an analytical survey usinga cross-sectional approach and is an analytical survey study. Total sampling was employed to establish the sample size for this study, which had an 82-person population and sample size. Observation and interviews were used to collect information. Data was analyzed using the chi-square test. The variables of mother's knowledge (0.003), mother's education (0.037), mother's occupation (0.039), eating parenting (0.012), health parenting (0.028), and hygiene parenting (0.010) had a significant relationship with the incidence of malnutrition in children under five in the Kori Health Center Work Area, Southwest Sumba Regency. Associated agencies, such as the health office and public health center officers, are expected to continue to encourage community health promotion, particularly for individuals living in remote areas with limited access